ESTABLISHMENT OF PROFESSIONAL COMPETENCE SYSTEMS OF HIGHER EDUCATION TRAINING OF TEACHERS OF TECHNOLOGY - O.B. Loshtun (Academy of Cognitive and Natural Sciences, 2008)
In the article the basic constituents of professional competence of future teachers of technology are examined by introduction to the educational process of the special trainings of seIf-know ledge.